Remote identification of fluvial knickzones and their imprints on landscape morphology in the passive margins of Western Arabia. (July 2016) - Yunus, Ali P.; Oguchi, Takashi; Hayakawa, Yuichi S.
Abstract: Fluvial knickzone identification and understanding the degree to which they propagate in a channel have been recently received much attention in landscape studies. A significant amount of research in the past decade around the globe demonstrated the role of climatic, base-level change and tectonic control on unusual channel profiles. However, less attention is paid to the fluvial systems in well-developed arid to semi-arid mountain escarpments and the highlands of the Arabian Peninsula. For the first time in this region, knickzone analysis was conducted by using changing rate of river gradient at different scales. This article assesses 5121 km length of longitudinal river profiles in 36 basins extracted from a digital elevation model (DEM) for morphological quantification and comparisons of knickzones, and discusses the landscape forms and origin. A total of 325 knickzones were identified, and the length of the identified knickzones is 83.76 km. Knickzone frequency is estimated as 0.063 km −1, whereas knickzone density is 1.63%. The results suggest that knickzone frequency and knickzone density vary according to bedrock types. The knickzones tend to be positively correlated with mean annual precipitation, thus confirm a coupled climatic and bedrock control on their formation. Highlights: First comprehensive knickzone research on steep drainages of the Arabian Peninsula. Semi-automated technique applied to identify knickzones from channel profiles. 325 knickzones are identified from 5121 km-long streams in 36 basins. Their form, development, and influence on shaping the basins are discussed.